Investigating Morphogenesis in Xenopus Embryos: Imaging Strategies, Processing, and Analysis - Kim, Hye Young (Cold Spring Harb Protoc, 2013)
Methods have been developed for visualizing cell movement and protein dynamics during morphogenesis within live multicellular tissues isolated from Xenopus laevis embryos. These include the preparation and use of reporter constructs in Xenopus embryos, microsurgical techniques for isolating embryonic tissues, and methods for culturing live tissues for extended periods. In this article, we present strategies for successful imaging of large thick embryonic tissues by improving the signal and minimizing damage to cells and tissues from overexposure. We also describe strategies for image analysis, including construction of kymographs, use of time- and z-projected confocal stacks, and approaches to segment images using regions of interest. With these imaging tools, the “cut-and paste” embryology of the Xenopus model system allows remarkable access to both the mechanics of cells and tissues as well as the complex cell biology of adhesion and cytoskeleton during morphogenesis.